Fabrication of defects in 3D printed materials for ultrasonic analysis - Sim, Qin Li (Nanyang Technological University, 2024)
Ultrasonic testing (UT) is widely used to detect the presence of defects typically in denser materials such as metals. Its application to 3D printed plastics presents unique challenges due to high attenuation of ultrasound in such materials. This project investigates the feasibility of UT on Polylactic Acid (PLA) specimens fabricated via Fused Deposition Modelling (FDM) and explores the effects of different factors such as probe frequency and defect characteristics on UT dimensional accuracy. Straight-beam UT probes of frequencies 0.5 MHz to 20 MHz were used alongside an automatic ultrasonic C-scan machine to obtain C-scan and A-scan displays of embedded defects within the printed specimens. The six experiments conducted highlighted the importance of having a small transducer area relative to the size of the defect. High probe frequencies could size defects more accurately though the signal-to-noise ratio would be lower, and scans conducted from top surfaces of specimens with respect to the build orientation faced problems in the presence of overhanging material within the specimen. Despite advancements, challenges persist in achieving reproducible and accurate UT results in 3D printed specimens, attributed to the high ultrasound attenuation which is exacerbated by low infill density.